The Effect of Indonesia’s Presidential Election on the Indonesian Stock Market - Sahetapy, Kenneth August; Tanasale, Amelia (Paradoks : Jurnal Ilmu Ekonomi, 2024)
Political events that happen tend to affect the stability and the condition of the economy. One of the most important political events that happens in a country is a presidential election as it can greatly affect the direction of that nation for the next few years. This research analyses the effect of Indonesia’s 2024 presidential election season on the stock price of Indonesia’s leading firms (LQ45). By using the paired sample t-test method to analyse three events surrounding the elections namely, the registration of the candidates, the election, and the announcement of the ruling from the election dispute, this research found that the registration of certain candidates negatively affect stock prices while another candidate registration has no significant effect on stock prices. Meanwhile, the election itself is found to have a positive effect on stock prices, while the ruling of the lawsuit does not affect stock prices. This shows that certain political events do affect stock prices while on other events, the market does not react significantly to the events